The BOBS-System - Eriksen, Søren Henrik; Jensen, Bent Bæk; Kristensen, Bent Bruun; Madsen, Ole Lehrmann (DAIMI Report Series, 1982)
The BOBS system is an LALR(1) parser-generator. This paper is a user manual for the system consisting of a general description of the system, a reference manual, and a summary of parsing terminology. The sections can be read without knowledge of parsing theory. Furthermore, the implementation of the system is described. This is done by giving references to literature containing descriptions of some of the algorithms used, and by giving abstract algorithms for other parts of the system. This section requires familiarity with LR-parsing. Second edition (first edition 1977).